2019
DOI: 10.1063/1.5122774
|View full text |Cite
|
Sign up to set email alerts
|

A low-power and high-sensitivity magnetic field sensor based on converse magnetoelectric effect

Abstract: Tremendous progress has been made in boosting the realization of magnetoelectric (ME) magnetometers based on the direct ME effect (DME) for bulk ME laminates. In this work, we studied the potential of an electrically driven bulk magnetic field sensor based on the converse ME effect (CME). Starting from a discussion about the dependence of the induced voltage from the pickup coil on coil parameters and the CME coupling process, we then experimentally measured the optimized bias field in the off resonance region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In 2011, frequency conversion technology (FCT) was proposed to circumvent the large 1/f noise for active ME sensors [56][57][58][59][60]. Quasi-static or extremely-low frequency magnetic fields can be effectively detected in this case.…”
Section: Low-frequency Magnetic Sensormentioning
confidence: 99%
“…In 2011, frequency conversion technology (FCT) was proposed to circumvent the large 1/f noise for active ME sensors [56][57][58][59][60]. Quasi-static or extremely-low frequency magnetic fields can be effectively detected in this case.…”
Section: Low-frequency Magnetic Sensormentioning
confidence: 99%
“…Chu et al [ 104 ], reported a ME magnetic field sensor based in the control of the magnetization via an applied electric field with a ME laminate composed by Pb(Mg 1/3 -Nb 2/3 )O 3 -Pb(Zr, Ti)O 3 (PMN-PZT) crystal, poled along the thickness direction and a pickup coil wound around the laminate. This laminate was electrically driven by the contacts deposited on the piezoelectric layer at the frequency of its first-order longitudinal vibration mode, and the induced voltage was captured by the pickup coil based on the law of electromagnetic induction, Figure 16 .…”
Section: Applications In the 40 Contextmentioning
confidence: 99%
“…The ME laminate show a sensitivity of 3400 V/T, the induced voltage was mainly proportional to the excitation voltage. The sensor also exhibited a limit of detection of ≈115 pT at 10 Hz and 300 pT at 1 Hz, with a power consumption of 0.56 mW [104]. Xu et al [105], developed a low frequency transmitter based on the capabilities of the ME resonance sensor.…”
Section: Applications In the 40 Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kuntal Ray et al theoretically proved that the magnetization switching time of the single-domain nanomagnet under the driving voltage applied on the magnetostrictive/piezoelectric multiferroic can be up to 10 ns [32], which implies that the modulation frequency of the novel modulation method can theoretically reach 100 MHz. Experimentally, Zhaoqiang Chu et al proposed a low-power and high-sensitivity magnetic field sensor based on a FE/FM multiferroic heterostructure, and the sensor operates well at high frequency up to 40 kHz [33]. Tianxiang Nan et al reported on nanomechanical magnetoelectric antennas with a FE/FM thin-film multiferroic heterostructure working at about 60 MHz.…”
Section: Materials Optimization Fe Layer and Fmf Layermentioning
confidence: 99%